Mental Accounting and Self-Control Over Daily Expenses of Students - Riza Amalia Rifani; Kamidin, Masruhi; Ramdani, Muh. Reza (Amsir Accounting & Finance Journal, 2024)
Daily life expenses are defined as a number of expenditures to produce or obtain a number of goods. For students undergoing studies, they are often faced with various problems and challenges in financial management. Students frequently have limitations in terms of income and expenses, making it difficult for them to manage their finances. Understanding that influences decision-making processes in controlling daily expenses is crucial. Mental accounting is an important psychological concept in financial decision-making. This study collected data from students in Parepare City, which was then processed using an application to form quantitative data. The study population consisted of all students registered at 3 campuses in Parepare City from various study programs and academic levels. In this research, the researcher utilized Probability Sampling known as Simple Random Sampling as the sample technique. The research findings indicate that mental accounting behavior and self-control have beneficial impacts on managing daily expenses for students. Students with high levels of mental accounting awareness show high consciousness of their daily spending patterns.